Exploring the Moderating Effect of Gender on the Relationship between Organizational Commitment and Organizational Citizenship Behavior - Masruroh, Rina; Iskandar; Dewi, Dhea Tresna (Asosiasi Ahli Administrasi Indonesia, 2024)
Lecturers in Kuningan Regency are expected to demonstrate high Organizational Citizenship Behavior to enhance organizational benefits and ensure that work is conducted more effectively and efficiently. This research aims to investigate the effect of gender as a moderating variable on the relationship between organizational commitment and OCB among these lecturers. The study employed a survey method with a quantitative approach, targeting a population of 346 lecturers from three universities in Kuningan Regency. Using a proportional random sampling technique, which divides the sample based on specific strata, a sample of 186 lecturers was selected. The findings indicate that organizational commitment has a positive and significant impact on OCB, and gender significantly moderates this relationship, enhancing the effect of organizational commitment on OCB.